The overland journey from Utah to California : wagon travel from the City of Saints to the City of Angels - Lyman, Edward Leo, 1942- (University of Nevada Press, 2004)
"The wagon trail between Salt Lake City and Los Angeles is one of the most important and least-known elements of nineteenth-century Western migration. Known as the Southern Route, it included the western half of the Old Spanish Trail and was favored because it could be used for travel and freighting year-round. It was, however, arguably the most difficult route that pioneers traveled with any consistency in the entire history of the country. Following not rivers but leading from one - sometimes dubious - desert watering place to the next and offering few havens for the sick, weary, or unfortunate."